(untitled) (El Taco en la Brea, 2022)
Although neoliberal globalization has been considered as a movement to expand the free circulation of goods in a world economic space, as a note, both economic and symbolic goods have encountered different constraints to cross borders. Trying to make an analysis that overcomes nationalism and methodological monolingualism, this article tries to give an account of the emergence of a publishing house founded in Cape Verde. Created in 2013 by the couple Filinto Elísio (Cape Verdean) and Márcia Souto (Brazilian), publishing house Rosa de Porcelana currently operates between the archipelago of Cape Verde and Portugal. It currently has a catalog of more than 50 books and since 2017 it has organized the World of Salt Literature Festival in its founding country, which, in partnership with several Portuguese, Brazilian and African institutions, tries to position itself as a meeting point and a bridge between the European, African and American continents. Based on an interview carried out with the editors, and on documentary research about their activities, this approach to their editorial and personal trajectory seeks a reflection on the struggle against colonial legacies that insist on being present and the search for the construction of new geographies and literary geopolitics postcolonials.